Editors’ Introduction: Labour, Care, and Just Transitions in Contemporary Asia - Asep Muhamad Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2024)
This JASSR Vol. 6, No. 1 (2024) presents the themes of labour, care, and just transitions in contemporary Asia. It approaches the issue as an inquiry into how digital, climate, energy, poverty-reduction, and care transitions reshape everyday lives, redistribute risks, and raise questions of fairness. The articles examine short-video entrepreneurship among Chinese smallholder farmers, climate education in Indonesia, Laos’s hydropower geopolitics, community resource mobilization among Dao households in Vietnam, and childcare facilities for working mothers in Dhaka. Together, they show that transition is not only a matter of technology, policy, or growth, but also a social process experienced through labour, welfare, ecological awareness, gender equality, community capacity, and the uneven burdens of development.